Priapulids and sipunculids dredged by the Swedish Antarctic Expedition 1901-1903 and the Phenomenon of bipolarity - Théel, Hjalmar, b. 1848; Svenska sydpolar-expeditionen (1901-1903) (Uppsala : Almqvist & Wiksells, 1911)
Mode of access: Internet.